Size at maturity, maturity stages, and sex ratio of Micropterus salmoides (Lacepède, 1802) in Zimbabwe’s largest inland reservoir, Tugwi Mukosi: a baseline study - Magqina, Terence; Mhere, Alfred (Journal of Fisheries, 2020)
Size at maturity, sex ratio and maturity stages are key population parameters that are important in fisheries management of exploited stocks as they influence survival of fish populations. The introduced largemouth bass Micropterus salmoides has successfully colonised freshwater bodies in southern Africa. In Tugwi Mukosi Dam, Zimbabwe’s largest reservoir, largemouth bass is a fish of importance as it provides tourism, food and income for the local communities. This study investigated population parameters of M. salmoides in Tugwi Mukosi Dam. The study revealed that the size at 50% sexual maturity (L50) value for male and female was 204 mm and 261 mm respectively. The logistic equation for female largemouth bass was M(L) = 1 / [1 + exp (–0.256L + 6.402)]. For male largemouth bass the logistic equation was M(L) = 1 / [1 + exp (–0.1375L + 4.129)]. The results showed that reproductive activity peaked in October. The male to female ratio was 1:1.04 which is typical of healthy populations. More research and monitoring of the population parameters of largemouth bass is needed so as to be able to predict long term effects of overexploitation and enable responsible authorities to protect the fish stock from collapsing.